An update on platelet-rich plasma (PRP) therapy in endometrium and ovary related infertilities: clinical and molecular aspects - Hajipour, Hamed; Farzadi, Laya; Latifi, Zeinab; Keyhanvar, Neda; Navali, Nazli; Fattahi, Amir; Nouri, Mohammad; Dittrich, Ralf (Systems Biology in Reproductive Medicine, 2021)
Administration of platelet-rich plasma (PRP) is one of the well-recommended strategies for the treatment of endometrium- and ovary-associated infertility. Due to the autologous source of PRP, minimal risks for disease transmission and immunogenic and allergic responses are expected in this method. Despite the extensive use of PRP in medicine, its precise mechanism of action in endometrial and ovarian tissues is still unknown. Nevertheless, the induction of cell proliferation, chemotaxis, regeneration, extracellular matrix synthesis, remodeling, angiogenesis, and epithelialization are the main pathways for PRP to affect female reproductive organs. Given the promising results of previous studies, it is necessary to standardize PRP preparation protocols for different therapeutic purposes and also clearly determine appropriate inclusion and exclusion criteria for recruiting patients. In the current review, we presented a summary of studies on PRP therapy for endometrium- and ovary-associated infertility with a focus on the possible mechanisms by which PRP enhances endometrial receptivity and regenerates ovarian function.
CRIS-Team WoS Importer:2021-03-19